HPV vaccine introduction in the Americas: a decade of progress and lessons learned. (2nd November 2022) - De Oliveira, Lucia H.; Janusz, Cara B.; Da Costa, Maria Tereza; El Omeiri, Nathalie; Bloem, Paul; Lewis, Merle; Luciani, Silvana
ABSTRACT: Introduction: Human papillomavirus (HPV) is an important public health concern due to its causative role in many cancers, especially cervical cancer, and other conditions that lead to serious health consequences in both men and women. In Latin America and the Caribbean, nearly 60, 000 new cases of cervical cancer and another 7, 000 HPV-associated cancers are diagnosed annually. Areas covered: HPV vaccination combined with comprehensive cervical cancer control programmingis paving the way for eliminating cervical cancer as a major public health problem and drastically reducing other HPV-associated diseases. To date, 44 countries and territories in the Americas have introduced HPV vaccines as part of their national immunization programs and cervical cancer control strategies. Early lessons from HPV vaccine introduction suggest that transparent and credible evidence-based decision-making, information, education and communication about HPV and cervical cancer, coordination with existing cervical cancer control initiatives, and precise planning for ensuring effective uptake of the vaccine in target groups are all critical elements of success. Expert opinion: There is an urgent need for strategies to increase HPV vaccine coverage, and as the integrated control programs evolve and other HPV-associated disease becomes important for public health, there will be a need for continued program and policy evaluation.